(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
The balancing process is based on mathematical modeling an a series of text phs represented by several variable mathematical sequences to solve the problem of balancing the calculation cost factors of the time of implementation of the encryption algorithm this process, a string of text characters represented by several variable mathematical consequences is divided into solving the problem of the balance between the mathematical cost factors represented by the time of implementation of the encryption algorithm and the safety coefficient associated with the length of the encryption key by calculating the number of operations executed per second that know what The complexity of the algorithm and the key length required for the encryption and decryption processes, in addition to focusing on several key factors during the implementation process, are called Storage Space and Processing Speed, Increasing Confidentiality. Emphasis is placed on the marginal point that must be considered a compatibility point between the confidentiality factor and the speed factor, and this point is determined according to the nature and size of the data transmitted through the use of cryptographic algorithms and variable mathematical functions to convert data and information into a mixture of symbols And numbers and letters using Cryptography rules.